Inorganic Phosphate Wet Foams Stabilization to Porous Ceramics by Direct Foaming - Pokhrel, Ashish; Nam Seo, Dong; Hyung Cho, Gae; Jin Kim, Ik (Asian Journal of Chemistry, 2013)
The optimization of inorganic hydroxyl foams with an admixture of calcium phosphates was done using an in situ particle-surface modifier through the process of direct foaming. The purpose of the study was to observe the behaviour of the hydroxyl apatite wet foams using admixtures in order to form highly stable wet foams to porous ceramics. Porous ceramics were formed utilizing a simple process, understanding the changes in the stability. The resulting microstructures occurred by adjusting the particle-amphiphile concentration and different ratios of additional additives in the initial suspension. The influence of different parameters were satisfactorily described in terms of balance between the stabilizer and controlling parameters as viscosity, contact angle, bubble size and porosity. Stabilized wet foams were formed, sintering at 1200 ºC for 2 h gave micro porous ceramics with porosity of more than 65 %.